Assignment of sugar arrangement in branched steviol glycosides using electrospray ionization quadrupole time‐of‐flight tandem mass spectrometry. (8th January 2017) - Perera, Wilmer H.; Avula, Bharathi; Khan, Ikhlas A.; McChesney, James D.
Abstract : Rationale: Steviol glycosides with an ent ‐kaurene core are being used in the Food Industry as non‐caloric sweeteners. These compounds are chemically similar in terms of sugar types and sugar arrangements. In order to assign sugar positions, we describe herein the dissociation pattern for steviol glycosides under varying collision energies. Methods: Steviol glycosides (1 mg/mL, 2 μL) were automatically injected into the mass spectrometer by direct infusion using a 100‐well tray autosampler. The mass spectrometric analysis was performed using a quadrupole time‐of‐flight (QTOF) tandem mass spectrometer (model #G6530A; Agilent Technologies, Palo Alto, CA, USA) equipped with an electrospray ionization (ESI) source with Jet Stream technology. Results: Dissociation of several natural and prepared steviol glycosides was carefully studied by ESI‐QTOF‐MS/MS using a range of collision energies: 10, 20, 30, 40, 50, 60, 70 and 80 eV. This procedure allowed us to establish the dissociation pattern for steviol glycosides, and thus the sugar arrangement in the branched oligosaccharide portion linked at position C‐13 of steviol, and also infer the sugar arrangement at C‐19. Conclusions: Those steviol glycosides with a monosaccharide or less hindered disaccharides at position C‐19 are cleaved at low collision energy (10 eV) while highly hindered disaccharides and trisaccharides are cleaved at 40 eV. However, sugars attached at C‐13 cleave at highest collision energies in the following order: the C‐3 sugar, followed by the C‐2 sugar and finally the sugar directly linked at C‐13. Copyright © 2016 John Wiley & Sons, Ltd.